Computational Network Pharmacology–Based Strategy to Capture Key Functional Components and Decode the Mechanism of Chai-Hu-Shu-Gan-San in Treating Depression - Wang, Kexin; Li, Kai; Chen, Yupeng; Wei, Genxia; Yu, Hailang; Li, Yi; Meng, Wei; Wang, Handuo; Gao, Li; Lu, Aiping; Peng, Junxiang; Guan, Daogang (Frontiers in Pharmacology, 2021)
Traditional Chinese medicine (TCM) usually play therapeutic roles on complex diseases in the form of formula. However, the multi-components and multi-targets characteristics of formulas bring great challenges to the mechanism analysis and secondary development of TCM in treating complex diseases. Modern bioinformatics provides a new opportunity for the optimization of TCM formula. In this report, a new bioinformatics analysis of computational network pharmacology model was designed, which takes Chai-Hu-Shu-Gan-San (CHSGS) treatment of depression as the case. In this model, effective intervention space was constructed to depict the core network of intervention effect transferred from component targets to pathogenic genes based on a novel node importance calculation method. The intervention-response proteins were selected from the effective intervention space, and the core group of functional components (CGFC) was pick out based on these intervention-response proteins. Results show that the enriched pathways and GO terms of intervention-response proteins in effective intervention space could cover 95.3% and 95.7% of the common pathways and GO terms that response to the major functional therapeutic effects. Additionally, 71 components from 1012 components were predicted as the CGFC, the targets of CGFC enriched in 174 pathways which cover the 86.19% enriched pathways of pathogenic genes. Based on the CGFC, two major mechanism chain were inferred and validated. Finally, the core component in CGFC were evaluated by in vitro experiments. These results indicate that the proposed model with good accuracy in screening the CGFC and inferring the potential mechanisms in the formula of TCM, which provides reference for the optimization and mechanism analysis of the formula in TCM.